\(f\left(x\right)=4x^3+4x^4-x^2+3x^2-3x^4-3x^3\)
\(\Leftrightarrow f\left(x\right)=\left(4x^3-3x^3\right)+\left(4x^4-3x^4\right)+\left(-x^2+3x^2\right)\)
\(\Leftrightarrow f\left(x\right)=x^3+x^4+2x^2\)
\(f\left(x\right)=0\)
\(\Leftrightarrow x^3+x^4+2x^2=0\)
\(\Leftrightarrow x^2\left(x+x^2+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2=0\\x+x^2+2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2+\dfrac{1}{2}x+\dfrac{1}{2}x+2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x\left(x+\dfrac{1}{2}\right)+\dfrac{1}{2}\left(x+\dfrac{1}{2}\right)+\dfrac{3}{2}=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\\left(x+\dfrac{1}{2}\right)^2+\dfrac{3}{2}>0\forall x\end{matrix}\right.\)
Vậy f(x) chỉ có 1 nghiệm